Assessment of HIV/AIDS literacy in 15- 49 years old people in Yasuj and its related factors - S Shariatinia; M Fararoei; K Karimzadeh Shirazi; M Shams (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: Health literacy is the capacity of an individual to obtain, interpret, and understand basic health information and services and the competence to use such information and services in ways that are health enhancing. The aim of this study was to assess the HIV/AIDS health literacy in Yasuj and its related factors.